The Nature of Hyperinflations between 1980 and 2008: A Case of Three Regions - Ndlovu, Sabelosenkosi (School of Economics, 2019)
This dissertation uses 13 year panel data to explore the nature of hyperinflations which occurred in 14 countries between the years 1980 and 2008. The countries are grouped into three geopolitical regions of Latin America, former states of the Union of Soviet Socialist Republics (USSR) and Africa. The analysis principally uses the quantity theory of money (QTM) and the purchasing power parity (PPP) as theoretical frameworks. The Dumitrescu-Hurlin panel causality is used to examine the nature of the relationship between exchange rates, money supply and price levels during the hyperinflationary periods. Notable similarities regarding the causal relationships, particularly between money supply, and price levels were found. Exchange rate depreciation-inflation spirals are examined using the PPP hypothesis. Over the 13 year periods under investigation, the findings suggest that prices and exchange rates did not tend to move together in all the cases. The impact of hyperinflations on the velocity of money is investigated for the three regional cases, following which the long-run relationship between QTM variables is tested using Pedroni residual co-integration. Despite the substantial dissimilarities in inflation rates and velocity in the countries, there seems not to be significant differences in the impact of hyperinflations on velocity. In examining whether a long-run or equilibrium relationship existed between inflation, money growth and real output during the hyperinflationary periods, the findings suggest it was not the case in all instances. Although the econometric results accord with findings in the relevant literature, it is apparent that despite the generic systematic features which typify the phenomenon, the hyperinflationary experiences have not been uniform and have taken different paths.